New perspectives of additional doping and restructuring of cast metal materials - E. I. Marukovich; S. M. Usherenko; Yu. S. Usherenko (Литьë и металлургия, 2019)
Possibilities of creation of composites with application of a method of super-deep penetration (SDP) are considered. At drifting of metals and alloys in a regime of super-deep penetration powdered particles penetrate to depths into tens and hundreds millimetres. Results are brought, that at driving in a metal lower die (in the enclosed system) powdered particles generate additional energy. The filaments (channels) doped by substance introduced by powders and synthesised materials are besides, shaped. It is shown, that doping in regime SDP is localised in reinforcing zones and occurs at the expense of a heading of a material of microparticles and synthesis in high pressure zones.